2014
DOI: 10.1073/pnas.1322558111
|View full text |Cite
|
Sign up to set email alerts
|

Integrating phase and composition of secondary organic aerosol from the ozonolysis of α-pinene

Abstract: Airborne particles are important for public health, visibility, and climate. Predicting their concentrations, effects, and responses to control strategies requires accurate models of their formation and growth in air. This is challenging, as a large fraction is formed by complex reactions of volatile organic compounds, generating secondary organic aerosol (SOA), which grows to sizes important for visibility, climate, and deposition in the lung. Growth of SOA is particularly sensitive to the phase/viscosity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
202
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(218 citation statements)
references
References 84 publications
13
202
0
1
Order By: Relevance
“…9 shows a photograph of a typical impaction pattern of trans-3-hexene SOA on a Ge ATR crystal. For comparison, the impaction pattern of SOA formed from a-pinene ozonolysis obtained in a previous study 54 in our lab using the same impactor is also shown. The trans-3-hexene SOA flows away from the centerline that is the initial area of impact on the ATR crystal.…”
Section: This Journal Is © the Owner Societies 2015mentioning
confidence: 92%
See 3 more Smart Citations
“…9 shows a photograph of a typical impaction pattern of trans-3-hexene SOA on a Ge ATR crystal. For comparison, the impaction pattern of SOA formed from a-pinene ozonolysis obtained in a previous study 54 in our lab using the same impactor is also shown. The trans-3-hexene SOA flows away from the centerline that is the initial area of impact on the ATR crystal.…”
Section: This Journal Is © the Owner Societies 2015mentioning
confidence: 92%
“…48,51 In the present study, particle impaction/ATR-FTIR measurements were performed to offer some insight into the phase/viscosity of trans-3-hexene SOA since the impaction patterns on the Ge crystal have been shown to be an indicator of phase. 54 For example, viscous liquid particles hit and stick to the crystal to form a row of spots, whereas solid particles above a certain size bounce and can be subsequently captured on the crystal, forming a disperse pattern dubbed ''clouds''. 54 Fig.…”
Section: This Journal Is © the Owner Societies 2015mentioning
confidence: 99%
See 2 more Smart Citations
“…An aerosol's viscous state also has direct implications on the particle morphology, phase behaviour, optical properties, aging processes and lifetime. At the same time, only few direct measurement methods are available for monitoring such properties 1, [6][7][8][9][10][11][12][13][14][15][16] . Recently, we have demonstrated that viscosity of model organic aerosols, such as oleic acid droplets, and secondary organic aerosols (SOA) produced from the oxidation of myrcene or -pinene can be measured and imaged in a spatially and time-resolved manner using Fluorescence Lifetime Imaging Microscopy (FLIM) of molecular rotors 17 .…”
Section: Introductionmentioning
confidence: 99%